Legal frameworks for regulating digital nomad mobility: international experience and kazakhstani realities - Bokayev, Б.Н.; Nauryzbek, М.Д.; Nauryzbek, К.Д. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The article examines contemporary practices of regulating intellectual migration and new instruments for attracting mobile professionals, including visa regimes for digital nomads and diaspora engagement programs. Based on the policy transfer approach, a comparative analysis of five jurisdictions (Spain, Portugal, Estonia, Croatia, UAE) is conducted, identifying their key features and common elements. The Kazakhstani context is analyzed through strategic documents, legislative initiatives, and empirical data from surveys of graduates of foreign universities. The analysis demonstrates that current state policy is primarily focused on attracting and repatriating foreign specialists, while flexible mechanisms for the remote engagement of Kazakhstan’s own citizens abroad remain underdeveloped. The article suggests viewing international experience as an opportunity to adapt more convenient and modern tools for working with digital nomads and the diaspora.